Raman amplifier-soliton compressor and its application to all-channel hybrid OTDM demultiplexing - Ismail I.; Matsuura M.; Kishi N.; Nguyen-The Q. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by Scopus/WOS